Grinding composition

The polishing composition for Ni-P substrates, which incorporates a nonionic surfactant with oxyethylene units, addresses the challenge of reducing scratches and maintaining a high polishing rate, thereby enhancing the efficiency of the finishing polishing process.

JP7666904B2Active Publication Date: 2025-04-22FUJIMI INCORPORATED
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020164592
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-30
Publication Date
2025-04-22
Estimated Expiration
2040-09-30

AI Technical Summary

Technical Problem

The existing polishing compositions for finishing polishing of Ni-P substrates tend to reduce the polishing rate, leading to longer processing times for achieving the target surface accuracy, while also increasing the occurrence of scratches on the substrate surface.

Method used

A polishing composition is developed that includes abrasive grains, an acid, water, and a nonionic surfactant (Additive A) with oxyethylene units, which reduces scratches and maintains the polishing rate by improving dispersion stability and preventing abrasive grain contact.

Benefits of technology

The proposed polishing composition effectively reduces scratches on the Ni-P substrate surface while maintaining a high polishing rate, thereby reducing the time required to achieve the target surface accuracy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666904000001
    Figure 0007666904000001
Patent Text Reader

Abstract

To provide a polishing composition that is used in the finish polishing of an Ni-P substrate to suppress a decrease in polishing rate while allowing reduction in scratches.SOLUTION: The inventive polishing composition for the finish polishing of a Ni-P substrate contains an abrasive grain, an acid, and water and further contains an additive A. The additive A is a nonionic surfactant containing 85 wt.% or less of oxyethylene units in each molecule.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing composition, and more particularly to a polishing composition for magnetic disk substrates used for finish polishing of nickel-phosphorus plated magnetic disk substrates. [Background technology]

[0002] Conventionally, the manufacturing process of magnetic disk substrates, which require a highly accurate surface, includes a step of polishing the substrate (substrate to be polished), which is the raw material of the substrate, with a polishing liquid. For example, in the manufacture of a nickel-phosphorus-plated disk substrate (hereinafter also referred to as Ni-P substrate), polishing that places emphasis on polishing efficiency (primary polishing) and final polishing (finish polishing) that is performed to achieve the surface accuracy of the final product are generally performed. Patent Document 1 is an example of a technical document related to a polishing composition used for polishing magnetic disk substrates. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2007-092064 A Summary of the Invention [Problem to be solved by the invention]

[0004] A polishing composition used in the finish polishing of Ni-P substrates is required to have few defects (e.g., scratches) on the surface of the substrate to be polished by polishing with the polishing composition. Regarding the reduction of the above defects, Patent Document 1 describes that scratches are reduced by adding a compound selected from azoles and their derivatives to a magnetic disk substrate polishing composition. However, the technology described in Patent Document 1 is based on the technical idea that the compound selected from azoles and their derivatives exerts a scratch reducing effect by forming a protective film on the surface of the substrate to be polished (paragraph 0021 of Patent Document 1), so the polishing rate tends to decrease with the manifestation of the scratch reducing effect. When the polishing rate in the finish polishing decreases, the polishing time required to achieve the target surface precision tends to become longer. Therefore, it would be useful to provide a technology that reduces scratches while suppressing the decrease in the polishing rate in the finish polishing of magnetic disk substrates.

[0005] The present invention has been made in view of the above circumstances, and aims to provide a polishing composition that can be used for the finish polishing of Ni-P substrates, and can reduce scratches while suppressing the decrease in polishing rate. Another related aim is to provide a method for manufacturing a magnetic disk substrate using such a polishing composition. [Means for solving the problem]

[0006] According to this specification, a polishing composition is provided that is used for finish polishing of a nickel-phosphorus plated magnetic disk substrate. This polishing composition contains abrasive grains, acid, water, and further contains additive A. Additive A is a nonionic surfactant containing 85% by weight or less of oxyethylene units in the molecule. A polishing composition having such a composition can reduce scratches (uneven defects) while suppressing a decrease in the polishing rate. Hereinafter, the oxyethylene units (CH 2 CH 2 O units) is sometimes written as "OE units".

[0007] In some preferred embodiments, the additive A is a compound having a structure in which an oxyethylene unit and a hydrocarbon group are bonded by an ether bond or an ester bond. A polishing composition containing the additive A having such a structure can preferably exhibit the effect of reducing scratches while suppressing the decrease in polishing rate.

[0008] Preferably, the additive A is a compound having one or two chain hydrocarbon groups having a carbon number of 8 to 20. A polishing composition containing the additive A having such a structure can preferably exhibit the effect of reducing scratches while suppressing a decrease in the polishing rate.

[0009] Preferably, the additive A is a compound having 25 or less OE units. A polishing composition containing the additive A having such a structure can preferably exhibit the effect of reducing scratches while suppressing a decrease in the polishing rate.

[0010] In some embodiments of the polishing composition, the content of the additive A is less than 0.1 mM. At a concentration of the additive A in the above range, the effect of reducing scratches and suppressing a decrease in the polishing rate can be preferably exhibited.

[0011] The polishing composition according to some embodiments has a pH of less than 3.0. In such a pH environment, the effects of applying the technology disclosed herein can be preferably exhibited.

[0012] The abrasive grains preferably have an average primary particle size of 1 nm or more and 50 nm or less. By performing finish polishing using a polishing composition containing such abrasive grains, high surface quality can be efficiently achieved.

[0013] As the abrasive grains, silica grains can be preferably used. In a polishing composition containing silica grains as abrasive grains, the effects of the technology disclosed herein can be preferably exhibited.

[0014] This specification also provides a method for producing a magnetic disk substrate. The method includes a step of finish-polishing a substrate to be polished having a nickel-phosphorus plating layer using any of the polishing compositions disclosed herein. This method can efficiently produce a magnetic disk substrate (Ni-P substrate) having a high-quality surface with few scratches. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Preferred embodiments of the present invention will be described below. Note that matters other than those specifically mentioned in this specification that are necessary for carrying out the present invention can be understood as design matters for a person skilled in the art based on the prior art in the relevant field. The present invention can be carried out based on the contents disclosed in this specification and the technical common sense in the relevant field.

[0016] <Polishing composition> (Abrasive grain) The polishing composition disclosed herein contains abrasive grains. The abrasive grains have the function of mechanically polishing the surface of the substrate to be polished. The material and properties of the abrasive grains are not particularly limited, and can be appropriately selected according to the purpose and mode of use of the polishing composition. Examples of the abrasive grains include inorganic particles, organic particles, and organic-inorganic composite particles. Specific examples of inorganic particles include oxide particles such as silica particles, alumina particles, cerium oxide particles, chromium oxide particles, titanium dioxide particles, zirconium oxide particles, magnesium oxide particles, manganese dioxide particles, zinc oxide particles, and red iron oxide particles; nitride particles such as silicon nitride particles and boron nitride particles; carbide particles such as silicon carbide particles and boron carbide particles; diamond particles; carbonates such as calcium carbonate and barium carbonate; and the like. Examples of the alumina particles include α-alumina, intermediate aluminas other than α-alumina, and composites thereof. Intermediate alumina is a general term for alumina particles other than α-alumina, and specific examples include γ-alumina, δ-alumina, θ-alumina, η-alumina, κ-alumina, and composites thereof. Specific examples of organic particles include polymethylmethacrylate (PMMA) particles, poly(meth)acrylic acid particles, polyacrylonitrile particles, and the like. Here, (meth)acrylic acid refers to acrylic acid and methacrylic acid in a comprehensive sense. The abrasive grains can be used alone or in combination of two or more types. For example, two or more types of abrasive grains can be appropriately combined so that one or two or more of the physical property values ​​such as the average primary particle size and the average aspect ratio described below are within the desired range.

[0017] A suitable example of the abrasive grain in the technology disclosed herein is silica grain. The silica grain may be various silica grains mainly composed of silica. Here, the silica grains mainly composed of silica refer to grains in which 90% by weight or more, preferably 95% by weight or more, more preferably 98% by weight or more of the grains are silica. The abrasive grain in the technology disclosed herein may contain one type of such silica grains alone or two or more types in combination. For example, two or more types of silica grains may be appropriately combined so that one or two or more of the physical property values ​​such as the average primary particle size and the average aspect ratio of the abrasive grains are within the desired range. Examples of silica particles include, but are not limited to, colloidal silica (e.g., sodium silicate silica, alkoxide silica, etc.), fumed silica, precipitated silica, etc. Surface-modified silica particles may also be used. The surface modification may be, for example, chemical modification such as introduction of functional groups or metal modification.

[0018] A suitable example of silica particles that can be used as an abrasive in the technology disclosed herein is colloidal silica. Among them, it is preferable to use colloidal silica synthesized through particle growth in an aqueous phase, such as sodium silicate silica or alkoxide silica. This type of colloidal silica can suitably achieve a high polishing rate and good surface accuracy. When silica particles are used as abrasives, the colloidal silica contained in the abrasives may be one type, or two or more types with different manufacturing conditions and / or physical properties. In addition, the abrasives may be composed of one or more types of colloidal silica, or may be composed of a combination of colloidal silica and other silica particles (i.e., silica particles other than colloidal silica). In a preferred embodiment, the abrasives contained in the polishing composition contain colloidal silica (e.g., sodium silicate silica) alone. By using colloidal silica alone, a better surface accuracy (e.g., a surface with a reduced number of scratches) can be achieved while maintaining a high polishing rate.

[0019] In the technology disclosed herein, the particle shape of the abrasive grains (e.g., silica particles such as colloidal silica) is not particularly limited, and may be, for example, spherical or non-spherical. Specific examples of non-spherical shapes include a peanut shape, a cocoon shape, a shape with projections, and a rugby ball shape. The peanut shape may be, for example, the shape of a peanut shell. The shape with projections may be, for example, the shape of a confetti candy. In the polishing composition disclosed herein, it is preferable to use abrasive grains having a shape close to a sphere.

[0020] In the technology disclosed herein, the average primary particle diameter of the abrasive grains (e.g., silica particles) is not particularly limited and may be, for example, 1 nm or more. The average primary particle diameter is preferably 3 nm or more, more preferably 5 nm or more, even more preferably 10 nm or more, for example, 15 nm or more. By increasing the average primary particle diameter, a higher polishing rate tends to be realized. In addition, from the viewpoint of obtaining a surface with higher surface accuracy, the average primary particle diameter is preferably 50 nm or less, more preferably 45 nm or less, even more preferably 40 nm or less, and particularly preferably 35 nm or less. In some embodiments, the average primary particle diameter may be, for example, 30 nm or less, 25 nm or less, or 20 nm or less.

[0021] In this specification, the average primary particle size is calculated by the following formula: average primary particle size (nm) = 6000 / (true density (g / cm)) based on the specific surface area (BET value) measured by the BET method. 3 ) × BET value (m 2 The specific surface area is the particle size (BET particle size) calculated by the formula: (a) specific surface area (μm / g). The specific surface area can be measured using, for example, a surface area measuring device manufactured by Micromeritics, Inc., under the trade name "Flow Sorb II 2300."

[0022] Although not particularly limited, the average aspect ratio of the whole particles in the cumulative particle size distribution based on the number of abrasive grains is in principle 1.0 or more, and may be, for example, 1.02 or more, 1.05 or more, or 1.08 or more from the viewpoint of polishing efficiency. In addition, from the viewpoint of efficiently increasing the surface precision, the average aspect ratio of the whole particles is suitably 1.30 or less. By reducing the average aspect ratio of the whole particles, the particles can be easily rolled and moved, so that the processing is stable and scratches can be more preferably reduced. The average aspect ratio of the whole particles is preferably 1.25 or less, more preferably 1.20 or less, and may be 1.15 or less. Here, the average aspect ratio of the whole particles in the cumulative particle size distribution based on the number of abrasive grains refers to the average value of the major axis / minor axis ratio of each particle constituting the abrasive grain, that is, the number average aspect ratio. Hereinafter, unless otherwise specified, the average aspect ratio in this specification means the number average aspect ratio.

[0023] In some embodiments, the D of the abrasive grains 0-5 The average aspect ratio of the particles is, in principle, 1.0 or more, and the lower limit is not particularly limited, but may be, for example, 1.05 or more, and may be 1.08 or more. 0-5 The term "particles" refers to particles having a particle diameter that falls within the range of 0 to 5% of the cumulative particle diameter from the small diameter side in the cumulative particle size distribution based on the number of abrasive grains (cumulative number distribution from the small diameter side). The cumulative number distribution is typically represented by a curve in a graph with the horizontal axis representing particle diameter and the vertical axis representing cumulative number (%), which extends from the end (lower left) of the cumulative 0% and the small diameter side of the particle diameter to the upper right and reaches the end (upper right) of the cumulative 100% and the large diameter side of the particle diameter. D 0-5 The particles are small diameter particles that occupy 5% by number from the small diameter side. From the viewpoint of better reducing scratches, etc., in some embodiments, 0-5The average aspect ratio of particles should normally be 1.25 or less. Generally, even if particles have a relatively high overall sphericity, the small diameter side may contain irregularly shaped particles whose shape is distorted from a sphere. In such cases, the small irregularly shaped particles act as wedges against spherical particles, making it difficult for the particles to roll locally even if the particles as a whole have a high sphericity, which may result in scratches on the surface after polishing. D 0-5 By reducing the average aspect ratio of the particles, small-diameter particles that can form the above-mentioned wedges become more spherical in shape. Small-diameter particles with high sphericity are less likely to form the above-mentioned wedges during polishing, so there is less chance of the particles becoming locally difficult to roll. This, combined with the effect of using additive A, can more effectively reduce scratches. D 0-5 The average aspect ratio of the particles is preferably 1.24 or less, more preferably 1.23 or less, and even more preferably 1.22 or less.

[0024] The number-average aspect ratio of the abrasive grains is measured, for example, by the following method. That is, a transmission electron microscope (TEM, Hitachi High-Technologies Corporation STEM HD-2700) is used to photograph a predetermined number of particles (typically 1000 or more) observable by TEM contained in the abrasive grains to be measured at a magnification (for example, 200000 to 400000 times) that allows about 100 particles to be observed in one field of view, and a TEM image is obtained. Then, for the smallest rectangle circumscribing each particle image, the value obtained by dividing the length of its long side (long axis value) by the length of its short side (short axis value) is calculated as the long axis / short axis ratio (aspect ratio) of each particle. In addition, the area of ​​each particle is calculated from the image of each particle, and the diameter of an ideal circle (perfect circle) having the same area as the calculated area is calculated as the particle diameter of each particle. The cumulative particle size distribution of the abrasive grain to be measured is obtained by plotting the particle diameter calculated above for each particle constituting the abrasive grain on the horizontal axis and the cumulative number (%) on the vertical axis. Then, the aspect ratio of each particle having a particle diameter that falls within the range of 0 to 5% cumulative from the small diameter side in the cumulative particle size distribution is arithmetically averaged to obtain D 0-5The average aspect ratio of the particles can be obtained. In addition, the average aspect ratio of all particles can be obtained by arithmetically averaging the aspect ratios of all particles (i.e., the above-mentioned predetermined number of particles) in the cumulative particle size distribution. The above-mentioned average aspect ratio can be obtained, for example, using image analysis software MacView manufactured by Mountech Co., Ltd. In addition, the above-mentioned predetermined number, i.e., the number of particles for which the aspect ratio of each particle is calculated, is suitably 1000 or more, preferably 1500 or more, from the viewpoint of improving measurement accuracy and reproducibility. There is no particular upper limit to the above-mentioned predetermined number. From the viewpoint of measurement efficiency, the above-mentioned predetermined number may be, for example, 5000 or less, or may be 2500 or less.

[0025] The content of abrasive grains in the polishing composition disclosed herein is not particularly limited, but is typically 0.5% by weight or more, preferably 1% by weight or more, and more preferably 3% by weight or more. When multiple types of abrasive grains are contained, the above content is the total content of them. By increasing the content of abrasive grains, a higher polishing rate tends to be realized. From the viewpoint of the surface smoothness of the substrate after polishing and the dispersion stability of the abrasive grains, the above content is usually appropriate to be 25% by weight or less, preferably 20% by weight or less, more preferably 15% by weight or less, and even more preferably 10% by weight or less, for example 8% by weight or less.

[0026] In the polishing composition disclosed herein, the content of the abrasive grains in the solid content contained in the polishing composition is not particularly limited. From the viewpoint of easily exerting the effect of the present invention, the content of the abrasive grains is preferably 10% by weight or more of the total solid content, more preferably 20% by weight or more, and may be 30% by weight or more, 40% by weight or more, 50% by weight or more, 60% by weight or more, 80% by weight or more, 90% by weight or more, or 99% by weight or more. In some embodiments, the content of the abrasive grains may be 98% by weight or less of the total solid content, 95% by weight or less, 90% by weight or less, 85% by weight or less, or 80% by weight or less. In this specification, the solid content contained in the polishing composition refers to the residual content, i.e., the non-volatile content, after evaporating water from the polishing composition at a temperature at which the bound water that may be contained in the abrasive grains (e.g., silica particles) is not removed, for example, at 60°C.

[0027] The polishing composition disclosed herein can be preferably implemented in an embodiment that does not substantially contain alumina particles. Examples of the alumina particles include α-alumina particles. Such a polishing composition prevents quality degradation caused by the use of alumina particles. Examples of quality degradation include the occurrence of scratches and dents, residual alumina, and defects due to the penetration of abrasive grains. In this specification, "substantially free of a specific abrasive grain, for example, alumina particles," means that the proportion of the abrasive grains in the total solid content contained in the polishing composition is 1% by weight or less, more preferably 0.5% by weight or less, and typically 0.1% by weight or less. A polishing composition with a proportion of 0% by weight of alumina particles, that is, a polishing composition that does not contain alumina particles, is particularly preferred. In addition, the polishing composition disclosed herein can be preferably implemented in an embodiment that does not substantially contain α-alumina particles.

[0028] The polishing composition disclosed herein can be preferably implemented in an embodiment that does not substantially contain particles other than silica particles, i.e., non-silica particles.Here, "does not substantially contain non-silica particles" means that the proportion of non-silica particles in the total solid content contained in the polishing composition is 1% by weight or less, more preferably 0.5% by weight or less, and even more preferably 0.1% by weight or less.In such an embodiment, the application effect of the technology disclosed herein can be preferably exhibited.

[0029] The polishing composition disclosed herein can be preferably implemented in an embodiment that contains substantially only silica particles as abrasive grains.Here, "contains substantially only silica particles" means that the proportion of silica particles in the total solid content contained in the polishing composition is 99% by weight or more, more preferably 99.5% by weight or more, and even more preferably 99.9% by weight or more.In such an embodiment, the application effect of the technology disclosed herein can be preferably exhibited.

[0030] (acid) The polishing composition disclosed herein contains an acid. The acid functions to chemically polish the substrate to be polished. The acid may be either an inorganic acid or an organic acid. The acid may be used alone or in combination of two or more.

[0031] Specific examples of inorganic acids include phosphoric acid (orthophosphoric acid), nitric acid, sulfuric acid, hydrochloric acid, boric acid, sulfamic acid, phosphinic acid, phosphonic acid, pyrophosphoric acid, tripolyphosphoric acid, tetrapolyphosphoric acid, hexametaphosphoric acid, carbonic acid, hydrofluoric acid, sulfurous acid, thiosulfuric acid, chloric acid, perchloric acid, chlorous acid, hydroiodic acid, periodic acid, iodic acid, hydrobromic acid, perbromic acid, bromic acid, chromic acid, and nitrous acid.

[0032] Examples of the organic acid include organic carboxylic acid, organic phosphonic acid, organic sulfone, amino acid, etc. The number of carbon atoms contained in these organic acids is typically about 1 to 18, and preferably about 1 to 10, for example. Specific examples of organic acids include malonic acid, citric acid, isocitric acid, 1,2,4-butanetricarboxylic acid, maleic acid, malic acid, glycolic acid, succinic acid, itaconic acid, iminodiacetic acid, gluconic acid, lactic acid, mandelic acid, tartaric acid, formic acid, acetic acid, propionic acid, butyric acid, adipic acid, oxalic acid, valeric acid, enanthic acid, caproic acid, caprylic acid, pelargonic acid, capric acid, lauric acid, myristic acid, palmitic acid, margaric acid, stearic acid, cyclohexanecarboxylic acid, phenylacetic acid, and benzoic acid. Organic carboxylic acids such as crotonic acid, oleic acid, linoleic acid, linolenic acid, ricinoleic acid, methacrylic acid, glutaric acid, fumaric acid, phthalic acid, isophthalic acid, terephthalic acid, tartronic acid, glyceric acid, hydroxybutyric acid, hydroxyacetic acid, hydroxybenzoic acid, salicylic acid, methylenesuccinic acid, gallic acid, ascorbic acid, nitroacetic acid, oxaloacetic acid, chloroacetic acid, dichloroacetic acid, trichloroacetic acid, pyridine carboxylic acids such as nicotinic acid and picolinic acid; methyl acid phosphate, ethyl ester ... Chill acid phosphate, ethyl glycol acid phosphate, isopropyl acid phosphate, phytic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, aminotri(methylenephosphonic acid), ethylenediaminetetra(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), ethane-1,1-diphosphonic acid, ethane-1,1,2-triphosphonic acid, ethane-1-hydroxy-1,1-diphosphonic acid, ethanehydroxy-1,1,2-triphosphonic acid organic phosphonic acids such as ethanesulfonic acid, ethane-1,2-dicarboxy-1,2-diphosphonic acid, methanehydroxyphosphonic acid, 2-phosphonobutane-1,2-dicarboxylic acid, 1-phosphonobutane-2,3,4-tricarboxylic acid, α-methylphosphonosuccinic acid, aminopoly(methylenephosphonic acid); organic sulfonic acids such as ethanesulfonic acid, aminoethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, 2-naphthalenesulfonic acid, sulfosuccinic acid, 10-camphorsulfonic acid, taurine;Amino acids such as glycine, alanine, glutamic acid, aspartic acid, valine, leucine, isoleucine, serine, threonine, cysteine, methionine, phenylalanine, tryptophan, tyrosine, proline, cystine, glutamine, asparagine, lysine, and arginine;

[0033] Examples of preferred acids from the viewpoint of polishing efficiency include phosphoric acid, phosphonic acid, malonic acid, citric acid, maleic acid, hydrochloric acid, nitric acid, sulfuric acid, sulfamic acid, phytic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, etc. Among these, preferred acids include phosphoric acid, phosphonic acid, malonic acid, citric acid, and maleic acid.

[0034] The concentration [wt%] of the acid in the polishing composition (in the polishing composition containing a plurality of acids, the total of the acids) is not particularly limited. The concentration of the acid is usually 0.1 wt% or more, preferably 0.5 wt% or more, more preferably 0.8 wt% or more, further preferably 1 wt% or more, and may be 1.2 wt% or more. By increasing the concentration of the acid, a practical polishing rate tends to be easily obtained. The concentration of the acid in the polishing composition is usually 15 wt% or less, preferably 10 wt% or less, more preferably 5 wt% or less, and may be 3 wt% or less. By limiting the content of the acid, the surface precision of the polishing object (Ni-P substrate) is easily improved.

[0035] The acid may be used in the form of a salt of the acid. Examples of the salt include metal salts, ammonium salts, alkanolamine salts, etc. of the above-mentioned inorganic acids and organic acids. Examples of the metal salts include alkali metal salts such as lithium salts, sodium salts, and potassium salts. Examples of the ammonium salts include quaternary ammonium salts such as tetramethylammonium salts and tetraethylammonium salts. Examples of the alkanolamine salts include monoethanolamine salts, diethanolamine salts, and triethanolamine salts.

[0036] Specific examples of salts that can be contained in the polishing composition disclosed herein include alkali metal phosphates and alkali metal hydrogen phosphates such as tripotassium phosphate, dipotassium hydrogen phosphate, potassium dihydrogen phosphate, trisodium phosphate, disodium hydrogen phosphate, and sodium dihydrogen phosphate; alkali metal salts of the organic acids exemplified above; and, in addition, alkali metal salts of glutamic acid diacetate, alkali metal salts of diethylenetriaminepentaacetate, alkali metal salts of hydroxyethylethylenediaminetriacetate, and alkali metal salts of triethylenetetraminehexaacetate. The alkali metal in these alkali metal salts can be, for example, lithium, sodium, potassium, etc.

[0037] In some embodiments, the salt may preferably be an inorganic acid salt such as an alkali metal salt or an ammonium salt of an inorganic acid. For example, in addition to the above-mentioned alkali metal phosphates and alkali metal hydrogen phosphates, potassium chloride, sodium chloride, ammonium chloride, potassium nitrate, sodium nitrate, ammonium nitrate, etc. may preferably be used. Among them, preferred examples include alkali metal phosphates and alkali metal hydrogen phosphates. Alkali metal hydrogen phosphates are particularly preferred.

[0038] The acid and its salt can be used alone or in combination of two or more (e.g., two or three). In some preferred embodiments, the acid can be used in combination with a salt of an acid different from the acid. The acid is preferably an inorganic acid. The acid salt is preferably an inorganic acid salt.

[0039] The salt concentration is not particularly limited, and may be, for example, 0.01% by weight or more and 10% by weight or less. From the viewpoint of obtaining a higher usage effect, in some embodiments, the salt concentration may be, for example, 0.05% by weight or more, 0.1% by weight or more, or 0.2% by weight or more. The salt concentration is usually suitably 5% by weight or less, and may be 2% by weight or less, 1% by weight or less, or 0.5% by weight or less.

[0040] (water) The polishing composition disclosed herein typically contains water to disperse the abrasive grains in addition to the above-mentioned abrasive grains. As the water, ion-exchanged water, pure water, ultrapure water, distilled water, etc. can be preferably used. The ion-exchanged water can be, for example, deionized water.

[0041] (Additive A) The polishing composition disclosed herein contains additive A. Additive A is a nonionic surfactant containing 85% by weight or less of oxyethylene (OE) units in the molecule. By using such additive A, scratches can be reduced while suppressing a decrease in the polishing rate. Additive A can be used alone or in combination of two or more kinds.

[0042] The reason why such an effect is obtained is considered to be, for example, as follows. Additive A has a structure containing a specific amount of OE units in its molecule, and therefore exhibits moderate adsorption to abrasive grains (e.g., silica particles), which increases the dispersion stability of the abrasive grains and prevents contact between the abrasive grains, thereby suppressing the generation of coarse particles due to the aggregation of the abrasive grains, and can contribute to reducing scratches in the finish polishing of Ni-P substrates. In this way, since additive A exerts its effect mainly by adsorbing to the abrasive grains, it is considered that it can reduce scratches while suppressing the decrease in the polishing rate. Note that the above mechanism is the inventors' consideration based on experimental results, and the technology disclosed herein is not interpreted as being limited to the above mechanism.

[0043] Additive A OE unit content W OE (% by weight) is expressed by the following formula (1): W OE =M OE / M A ×100 (1) In the above formula (1), M OE is expressed in OE units (CH 2 CH 2 O) multiplied by the number of OE units contained in one molecule of additive A. M A is the molecular weight of additive A. OE unit (CH2 CH 2 As the molecular weight of O) and the molecular weight of additive A, the molecular weights calculated from the chemical formulas are used.

[0044] W OE The amount of additive A can be appropriately set within a range of 85% by weight or less so that the effect of using additive A can be obtained. OE For example, it may be 84% by weight or less, 83% by weight or less, less than 83% by weight, or 80% by weight or less. OE may be, for example, 70% by weight or less, 60% by weight or less, or 50% by weight or less. OE From the viewpoint of the adsorption of additive A to the abrasive grains, the content is suitably 1 weight % or more, may be 5 weight % or more, 15 weight % or more, 25 weight % or more, or may be 35 weight % or more.

[0045] The number of OE units per molecule of additive A can be appropriately selected so as to satisfy any of the above-mentioned OE unit contents and obtain an appropriate effect, and is not limited to a specific range. The number of OE units of additive A can be selected, for example, from the range of 1 to 60. In some embodiments, the number of OE units may be, for example, 40 or less, 30 or less or less than 30, 27 or less, 25 or less, 23 or less, or 21 or less, taking into consideration dispersion stability and the like. In addition, from the viewpoint of the adsorption of additive A to abrasive grains and the like, the number of OE units is suitably 2 or more, 3 or more, 4 or more, or 5 or more. The number of OE units means the average number of OE units in a mixture having different numbers of OE units.

[0046] A compound having one or more hydrophobic parts and one or more hydrophilic parts, at least one of which contains an OE unit, can be used as the additive A. From the viewpoint of ease of handling, the additive A that is liquid at room temperature (for example, about 25°C) can be preferably used.

[0047] The hydrophobic portion may be, for example, a hydrocarbon group, or may be a group containing an atom other than carbon and hydrogen (such as phosphorus, nitrogen, oxygen, sulfur, fluorine, chlorine, bromine, and iodine). In additive A having two or more hydrophobic portions, the hydrophobic portions may be the same or different. In some preferred embodiments, the hydrophobic portion contains a hydrocarbon group. The hydrocarbon group may be an aliphatic hydrocarbon group, or may be a hydrocarbon group containing an aromatic ring, such as an aryl group or an alkylaryl group. The aliphatic hydrocarbon group may be a saturated hydrocarbon group, or may be an unsaturated hydrocarbon group containing an unsaturated bond such as a carbon-carbon double bond, and may be linear or may contain a cyclic structure. The linear hydrocarbon group may be either linear or branched. Suitable examples of the hydrocarbon group constituting the hydrophobic portion include an alkyl group and an alkenyl group.

[0048] The number of hydrophobic moieties contained in the additive A and the number of carbon atoms contained in one hydrophobic moiety (e.g., a hydrocarbon group) can be selected so as to realize an appropriate OE unit content. From the viewpoint of easily exerting the effect of the hydrophobic moiety appropriately, the number of carbon atoms per hydrophobic moiety is suitably 6 or more, and may be 8 or more, 10 or more, 12 or more, 14 or more, or 16 or more. From the viewpoint of the dispersion stability of the additive A, the number of carbon atoms per hydrophobic moiety may be, for example, 24 or less, 22 or less, or 20 or less. In the additive A having two or more hydrophobic moieties, the total number of carbon atoms of the hydrophobic moieties may be, for example, 50 or less, 45 or less, or 40 or less. From the viewpoint of the dispersion stability, the number of hydrophobic moieties contained in the additive A is preferably 1 to 3, and more preferably 1 or 2.

[0049] The number of hydrophilic moieties contained in the molecule of Additive A may be, for example, about 1 to 8 (preferably 1 to 6). At least one of the hydrophilic moieties contains an OE unit. From the viewpoint of facilitating the appropriate exertion of the aggregation prevention effect, in some embodiments, the number of hydrophilic moieties containing an OE unit is suitably 1 to 6, preferably 1 to 4, and more preferably 1 or 2 per molecule of Additive A.

[0050] In the hydrophilic part containing OE units, the OE units are preferably continuous in two or more units. That is, additive A having a hydrophilic part containing a polyoxyethylene (POE) chain, which is a repeating structure of two or more OE units, is preferred. Additive A may have two or more hydrophilic parts containing OE units (for example, hydrophilic parts containing POE chains), for example, about 2 to 6 (preferably 2 to 3). In additive A having a hydrophilic part containing a POE chain, the repeat number of OE units in the POE chain may be, for example, 40 or less, 30 or less or less than 30, 27 or less, 25 or less, 23 or less, or 21 or less, from the viewpoint of easily exerting the aggregation prevention effect appropriately. In addition, from the viewpoint of the adsorption of additive A to abrasive grains, the repeat number of the OE units may be 3 or more, 4 or more, or 5 or more. In additive A having two or more hydrophilic parts containing POE chains, it is preferable that the total number of OE units contained in those hydrophilic parts satisfies the above repeat number.

[0051] Other examples of hydrophilic parts containing OE units include hydrophilic parts containing OE units and oxyalkylene units other than OE units (e.g., oxypropylene units, oxybutylene units). In this case, the number of oxyalkylene units other than OE units contained in such hydrophilic parts is preferably less than the number of OE units (e.g., 1 / 2 or less, 1 / 5 or less, or 1 / 10 or less of the number of OE units). In addition to the hydrophilic portion containing the OE unit, the additive A may have a hydrophilic portion not containing the OE unit. Examples of such hydrophilic portions include, but are not limited to, a hydroxyl group, an amide group, and an alkanol group having 1 to 2 carbon atoms.

[0052] In some embodiments, the additive A may have a structure in which a hydrophobic portion (e.g., a hydrocarbon group) and a hydrophilic portion containing an OE unit are linked via an ether bond or an ester bond. Examples of the additive A having such a structure include polyoxyethylene alkyl ethers, polyoxyethylene alkenyl ethers, polyoxyethylene alkyl esters, polyoxyethylene alkenyl esters, etc., provided that the OE unit content is equal to or less than the above-mentioned amount.

[0053] Preferred specific examples of additive A include polyoxyethylene 2-ethylhexyl ether, polyoxyethylene isodecyl ether, polyoxyethylene lauryl ether, polyoxyethylene isotridecyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene monolaurate, polyoxyethylene monooleate, polyoxyethylene dioleate, and the like, provided that the OE unit content is equal to or less than the above-mentioned specified amount.

[0054] The molecular weight of additive A may vary depending on the type of additive A, and is not limited to a specific range. From the viewpoint of appropriately exerting the effect of reducing scratches while suppressing the decrease in polishing rate, the molecular weight of additive A may be selected from the range of, for example, 200 or more and less than 4000. In some embodiments, the molecular weight of additive A may be, for example, 300 or more, 350 or more, 400 or more, 450 or more, 3000 or less, 2000 or less, 1400 or less, or 1200 or less. The molecular weight of additive A may be a molecular weight calculated from a chemical formula. When the nominal value of the molecular weight is disclosed by the manufacturer, the nominal value can be used.

[0055] The amount of additive A used can be set so that the effect of using the additive A (the effect of reducing scratches while suppressing the decrease in polishing rate) is appropriately exhibited, and is not limited to a specific range. The content of additive A in the polishing composition (when a plurality of types of additive A are contained, the total amount thereof) may be, for example, 0.001 mM or more (i.e., 0.001 mol / L or more), or may be 0.005 mM or more. From the viewpoint of further enhancing the effect of reducing scratches, in some embodiments, the content of additive A is suitably 0.01 mM or more, more preferably 0.02 mM or more, and even more preferably 0.03 mM or more. In addition, the content of additive A can be, for example, 1.0 mM or less, or may be 0.7 mM or less. From the viewpoint of suppressing the decrease in polishing rate, in some embodiments, the content of additive A is suitably less than 0.5 mM, preferably less than 0.2 mM, may be less than 0.15 mM, may be less than 0.1 mM, or may be less than 0.08 mM.

[0056] The content of additive A in the polishing composition (when a plurality of types of additive A are contained, the total amount thereof) can be, for example, 0.0001% by weight or more or 0.0003% by weight or more. From the viewpoint of enhancing the scratch reduction effect, the preferred content is 0.0005% by weight or more, and can be, for example, 0.001% by weight or more. From the viewpoint of suppressing the decrease in the polishing rate, the content of additive A in the polishing composition is suitably less than 0.1% by weight, preferably less than 0.5% by weight, more preferably less than 0.2% by weight, even more preferably less than 0.1% by weight, and may be less than 0.05% by weight, less than 0.03% by weight, or less than 0.01% by weight.

[0057] In the polishing composition disclosed herein, the content of additive A relative to 100 parts by weight of abrasive grains contained in the composition may be, for example, 0.001 parts by weight or more, preferably 0.003 parts by weight or more, and from the viewpoint of further enhancing the effect of reducing scratches, may be 0.005 parts by weight or more. In addition, from the viewpoint of suppressing the decrease in polishing rate, the content of additive A relative to 100 parts by weight of abrasive grains is appropriate to be 10 parts by weight or less, preferably less than 5 parts by weight, more preferably less than 2 parts by weight, even more preferably less than 1 part by weight, and may be less than 0.8 parts by weight, less than 0.5 parts by weight, or less than 0.3 parts by weight.

[0058] (Oxidizing agent) The polishing composition disclosed herein can contain an oxidizing agent as necessary.Examples of the oxidizing agent include, but are not limited to, peroxide, nitric acid or its salt, periodic acid or its salt, peroxo acid or its salt, permanganic acid or its salt, chromic acid or its salt, oxygen acid or its salt, metal salts, sulfuric acid, etc.The oxidizing agent can be used alone or in combination of two or more. Specific examples of the oxidizing agent include hydrogen peroxide, sodium peroxide, barium peroxide, nitric acid, iron nitrate, aluminum nitrate, ammonium nitrate, peroxomonosulfuric acid, ammonium peroxomonosulfate, metal peroxomonosulfate, peroxodisulfate, ammonium peroxodisulfate, metal peroxodisulfate, peroxolinic acid, peroxosulfuric acid, sodium peroxoborate, performic acid, peracetic acid, perbenzoic acid, perphthalic acid, hypobromous acid, hypoiodous acid, chloric acid, bromic acid, iodic acid, periodic acid, perchloric acid, hypochlorous acid, sodium hypochlorite, calcium hypochlorite, potassium permanganate, metal chromate, metal dichromate, iron chloride, iron sulfate, iron citrate, ammonium iron sulfate, etc. Preferred examples of the oxidizing agent include hydrogen peroxide, iron nitrate, periodic acid, peroxomonosulfuric acid, peroxodisulfuric acid, and nitric acid. It preferably contains at least hydrogen peroxide, and more preferably consists of hydrogen peroxide.

[0059] When the polishing composition disclosed herein contains an oxidizing agent, the content of the oxidizing agent in the polishing composition is preferably 0.01% by weight or more based on the amount of active ingredient, more preferably 0.05% by weight or more, even more preferably 0.1% by weight or more, and may be 0.2% by weight or more, or may be 0.3% by weight or more, in consideration of the rate of oxidation of the object to be polished and therefore the processability. Also, in view of improving the surface accuracy of the object to be polished, the content of the oxidizing agent in the polishing composition is preferably 5% by weight or less based on the amount of active ingredient, more preferably 1% by weight or less.

[0060] (Water-soluble polymer) The polishing composition disclosed herein may contain a water-soluble polymer as an optional component. The water-soluble polymer may protect the substrate during polishing and suppress the occurrence of scratches. The water-soluble polymer referred to here is a compound having a weight-average molecular weight (Mw) of about 2000 or more, typically 4000 or more. The water-soluble polymer may be a homopolymer or a copolymer. Examples of the water-soluble polymer include anionic polymers, nonionic polymers (excluding those corresponding to Additive A), cationic polymers, and amphoteric polymers. Examples of the water-soluble polymer include sulfonic acid polymers, polyacrylic acid and its salts, polyvinyl acetate, polymaleic acid, polyitaconic acid, polyvinyl alcohol, modified polyvinyl alcohol, polyglycerin, polyvinylpyrrolidone, copolymers of polyvinylpyrrolidone and polyacrylic acid and / or vinyl acetate, diallylamine hydrochloride sulfur dioxide copolymers, carboxymethylcellulose and its salts, hydroxyethylcellulose, hydroxypropylcellulose, pullulan, chitosan and its salts, etc., but are not limited thereto. The water-soluble polymers can be used alone or in combination of two or more.

[0061] From the viewpoint of dispersion stability of the polishing composition, anionic polymers may be preferably adopted in some embodiments. A preferred example of anionic polymers is a sulfonic acid polymer. The proportion of sulfonic acid polymers in the water-soluble polymers contained in the polishing composition disclosed herein may be, for example, 50% by weight or more and 100% by weight or less, preferably 70% by weight or more and 100% by weight or less, more preferably 90% by weight or more and 100% by weight or less, may be 95% by weight or more and 100% by weight or less, or may be 99% by weight or more and 100% by weight or less. Only one or more kinds of sulfonic acid polymers may be used as the water-soluble polymer.

[0062] Here, the sulfonic acid polymer refers to a polymer containing at least one type of repeating unit X having a sulfonic acid group as a repeating unit constituting the sulfonic acid polymer. The repeating unit X may be a repeating unit derived from a monomer having at least one sulfonic acid group in one molecule. Examples of the monomer having a sulfonic acid group include styrene sulfonic acid, isoprene sulfonic acid, vinyl sulfonic acid, allyl sulfonic acid, isoamylene sulfonic acid, 2-(meth)acrylamide-2-methylpropane sulfonic acid, and methallyl sulfonic acid. The sulfonic acid polymer may contain two or more types of the repeating unit X. The sulfonic acid polymer may further contain a repeating unit not having a sulfonic acid group. The repeating unit not having a sulfonic acid group may be a repeating unit having an anionic functional group other than sulfonic acid, or may be a repeating unit not having an anionic functional group.

[0063] An example of a repeating unit having an anionic functional group other than sulfonic acid is a repeating unit Y having a carboxy group. The repeating unit Y may be, for example, a repeating unit derived from (meth)acrylic acid. Here, "(meth)acrylic acid" is a concept that includes one or both of acrylic acid and methacrylic acid. The polishing composition disclosed herein may contain, as a sulfonic acid-based polymer, a (meth)acrylic acid / sulfonic acid copolymer containing a carboxy group-containing repeating unit Y and a repeating unit X derived from (meth)acrylic acid. Examples of the (meth)acrylic acid / sulfonic acid copolymer include a (meth)acrylic acid / isoprene sulfonic acid copolymer, a (meth)acrylic acid / 2-acrylamido-2-methylpropane sulfonic acid copolymer, and a (meth)acrylic acid / isoprene sulfonic acid / 2-acrylamido-2-methylpropane sulfonic acid copolymer. The (meth)acrylic acid / sulfonic acid copolymer may further contain a repeating unit that does not have a sulfonic acid group and is not derived from a (meth)acrylic acid monomer.

[0064] Other examples of sulfonic acid polymers include polyalkylarylsulfonic acid compounds such as naphthalenesulfonic acid-formaldehyde condensates, methylnaphthalenesulfonic acid-formaldehyde condensates, and anthracenesulfonic acid-formaldehyde condensates; melamine formalin resin sulfonic acid compounds such as melamine sulfonic acid-formaldehyde condensates; ligninsulfonic acid compounds such as ligninsulfonic acid and modified ligninsulfonic acid; and aromatic aminosulfonic acid compounds such as aminoarylsulfonic acid-phenol-formaldehyde condensates.

[0065] In some embodiments, a sulfonic acid polymer that does not contain a repeating unit Y having a carboxy group can be preferably used. A polishing composition that contains a sulfonic acid polymer that does not contain a repeating unit Y in combination with additive A tends to suppress the occurrence of defects (typically scratches) due to polishing. The sulfonic acid polymer that does not contain a repeating unit Y may further contain a repeating unit that does not have a sulfonic acid group or a carboxy group (for example, a repeating unit that does not have an anionic functional group).

[0066] A preferred example of the sulfonic acid polymer is a polymer in which the molar ratio of sulfonic acid group-containing repeating unit X to the total molar number of repeating units contained in the molecular structure of the polymer is 95% or more. For example, a sulfonic acid polymer substantially consisting of repeating unit X can be used as the water-soluble polymer. In such a sulfonic acid polymer, the molar ratio of the repeating unit X may be, for example, 98% or more, 99.5% or more, or 99.9% or more. In some embodiments of the polishing composition disclosed herein, a sulfonic acid polymer in which the molar ratio of the repeating unit X is 100%, that is, a sulfonic acid polymer consisting only of repeating unit X having a sulfonic acid group, can be preferably used as the water-soluble polymer. Examples of such sulfonic acid polymers include a homopolymer consisting of any one of the sulfonic acid group-containing monomers disclosed herein, and a copolymer consisting of two or more sulfonic acid group-containing monomers. Examples of the homopolymer include polystyrene sulfonic acid, polyisoprene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyisoamylene sulfonic acid, etc. Among these, polystyrene sulfonic acid, that is, a homopolymer of styrene sulfonic acid, is preferred.

[0067] The sulfonic acid polymer may be used in the form of a neutralized salt. Examples of the neutralized salt include alkali metal salts such as Na and K, ammonium salts, and alkylammonium salts. From the viewpoint of reducing defects, the sulfonic acid polymer may be preferably in the form of a salt other than Na salt (e.g., potassium salt), in the form of a cation-exchanged Na salt, or in the form of a non-neutralized salt.

[0068] The Mw of the water-soluble polymer (e.g., sulfonic acid polymer) may be, for example, 2000 or more, or 2500 or more. From the viewpoint of increasing the protection of the substrate surface and suppressing the occurrence of defects, in some embodiments, the Mw of the water-soluble polymer is preferably 3000 or more, more preferably 5000 or more, may be 7000 or more, or may be 9000 or more. The upper limit of the Mw of the water-soluble polymer is not particularly limited, and may be, for example, 1.5 million or less, 1 million or less, 500,000 or less, 300,000 or less, 200,000 or less, 100,000 or less, 70,000 or less, 50,000 or less, or 30,000 or less. In addition, the weight average molecular weight (water-based, polyethylene glycol equivalent) determined by GPC can be adopted as the Mw of the water-soluble polymer.

[0069] The concentration [wt%] of the water-soluble polymer (preferably, sulfonic acid polymer) in the polishing composition is not particularly limited. The concentration can be, for example, 0.0001 wt% or more. From the viewpoint of enhancing the protective effect of the substrate during polishing, the concentration is preferably 0.0005 wt% or more, more preferably 0.001 wt% or more, may be 0.002 wt% or more, may be 0.0025 wt% or more, or may be 0.003 wt% or more. In addition, from the viewpoint of favorably achieving both the protective property of the substrate during polishing and the cleaning removability from the substrate after polishing, the concentration of the water-soluble polymer is usually appropriate to be 0.2 wt% or less, preferably 0.15 wt% or less, for example 0.1 wt% or less, may be 0.07 wt% or less, or may be 0.05 wt% or less.

[0070] (Basic compounds) The polishing composition may contain a basic compound as necessary for the purpose of pH adjustment, etc. Here, the basic compound refers to a compound that has the function of increasing the pH of the polishing composition by being added to the composition. Examples of basic compounds include alkali metal hydroxides such as potassium hydroxide and sodium hydroxide, quaternary ammonium compounds such as quaternary ammonium hydroxide, ammonia, amines, etc. The basic compounds may be used alone or in combination of two or more.

[0071] (Other Ingredients) The polishing composition disclosed herein may further contain known additives that can be used in polishing compositions (for example, polishing compositions for magnetic disk substrates such as Ni-P substrates) such as surfactants other than additive A, chelating agents, preservatives, and antifungal agents, as necessary, within the scope that does not significantly impair the effects of the present invention. The surfactants other than additive A may be nonionic, anionic, cationic, or amphoteric. Examples of the preservatives and antifungal agents include isothiazolin-based preservatives such as 2-methyl-4-isothiazolin-3-one and 5-chloro-2-methyl-4-isothiazolin-3-one, paraoxybenzoic acid esters, phenoxyethanol, etc., but are not limited thereto. Alternatively, the polishing composition disclosed herein may be a composition that does not use one or more of the known additives exemplified above for the purpose of simplifying the composition, etc. In addition, the polishing composition disclosed herein may contain one or more compounds selected from the group consisting of azoles and their derivatives (hereinafter also referred to as azoles collectively) as desired, within the scope of not significantly impairing the effects of the present invention. Examples of azoles include triazole, tetrazole, imidazole, pyrazole, pyrrole, isothiazole, isoxazole, furazan, etc., among which benzotriazoles such as 1H-benzotriazole and 1,2,4-triazole are preferred. According to the technology disclosed herein, the use of additive A can reduce scratches while exhibiting a polishing rate roughly equal to or higher than that when additive A is not used, so that the use of additive A and azoles in appropriate combination can achieve a good balance between suppressing the decrease in polishing rate and reducing scratches at a higher level.

[0072] The pH of the polishing composition disclosed herein is not particularly limited, and may be selected, for example, from the range of 0.5 to 6.5. From the viewpoint of polishing efficiency, etc., the pH of the polishing composition is, for example, 4.0 or less, preferably 3.7 or less, more preferably 3.5 or less, may be 3.2 or less, may be 3.0 or less, more preferably less than 3.0, may be 2.5 or less, may be 2.2 or less. The pH of the polishing composition can be, for example, 1.0 or more, and from the viewpoint of suppressing roughness of the substrate surface after polishing, it is appropriate to make it higher than 1.0, may be 1.2 or more, preferably 1.4 or more, more preferably 1.5 or more (for example, more than 1.5), may be 1.7 or more, may be 1.8 or more, or may be 1.9 or more. In order to realize the above pH in the polishing liquid, a pH adjuster such as an organic acid, an inorganic acid, or a basic compound may be contained as necessary. The technique disclosed herein can be preferably implemented in an embodiment in which the pH of the polishing composition is 1.0 or more and 4.0 or less (for example, 1.5 or more and less than 3.0). The above-mentioned pH can be particularly preferably applied to a polishing composition for finish polishing of Ni-P substrates.

[0073] In the technique disclosed herein, the pH of the polishing composition can be determined by performing three-point calibration using a pH meter, then inserting a glass electrode into the composition to be measured. The standard solutions are, for example, oxalate pH standard solution: pH 1.68 (25°C), phthalate pH standard solution: pH 4.01 (25°C), neutral phosphate pH standard solution: pH 6.86 (25°C), and carbonate pH standard solution: pH 10.01 (25°C).

[0074] <Concentrate> The polishing composition disclosed herein may be in a concentrated form (i.e., in the form of a concentrated polishing liquid) before being supplied to the object to be polished (here, Ni-P substrate). Such a concentrated polishing composition (concentrate) is advantageous from the viewpoints of convenience and cost reduction during production, distribution, storage, etc. The concentration ratio can be, for example, about 1.5 to 20 times in terms of volume. From the viewpoint of storage stability of the concentrate, for example, a concentration ratio of about 2 to 10 times is appropriate. Such a concentrated liquid can be used in a form in which the polishing composition (polishing liquid) is prepared by diluting it at a desired timing and the polishing liquid is supplied to the object to be polished. The dilution can typically be performed by adding water to the concentrated liquid and mixing it.

[0075] <Multi-component polishing composition> The polishing composition disclosed herein may be a one-component type or a multi-component type, including a two-component type. For example, the polishing composition may be configured so that a part A containing some of the components (e.g., components other than water) of the polishing composition and a part B containing the remaining components are mixed and used for polishing an object to be polished. A preferred embodiment of the multi-component polishing composition is configured to contain a part A containing abrasive grains (typically a dispersion liquid further containing a dispersion medium for the abrasive grains) and a part B containing at least a part of the components other than the abrasive grains (e.g., acid, additive A, etc.). These are stored separately, for example, before use, and can be mixed at the time of use to prepare a one-component polishing composition. When mixed, an oxidizing agent such as hydrogen peroxide, water for dilution, etc. can be further mixed.

[0076] <Polishing process> The polishing composition disclosed herein can be suitably used for finish polishing of an object to be polished (here, a Ni-P substrate) in an embodiment including the following operations, for example. A preferred embodiment of the method for polishing an object to be polished using the polishing composition disclosed herein will be described below. That is, a polishing liquid (working slurry) containing any of the polishing compositions disclosed herein is prepared. The preparation of the polishing liquid may include adjusting the concentration (e.g., diluting) or adjusting the pH of the polishing composition to prepare the polishing liquid. Alternatively, the polishing composition may be used as it is as the polishing liquid.

[0077] Next, the polishing liquid is supplied to the object to be polished, and polished in a conventional manner. For example, the object to be polished is set in a general polishing device, and the polishing liquid is supplied to the surface of the object to be polished (the surface to be polished) through the polishing pad of the polishing device. Typically, the polishing liquid is continuously supplied, and the polishing pad is pressed against the surface of the object to be polished, and the two are moved relatively (for example, rotated).

[0078] Thereafter, the object to be polished is washed. For example, an alkaline washing step is carried out in which the object to be polished is washed with an alkaline washing liquid. The alkaline washing step typically includes contacting at least the surface of the object to be polished with an alkaline washing liquid. For example, the object to be polished can be brought into contact with the alkaline washing liquid by immersing the object to be polished in the alkaline washing liquid. An ultrasonic treatment may be carried out in which ultrasonic waves are applied to the object to be polished immersed in the alkaline washing liquid. In addition to or instead of applying ultrasonic waves, scrubbing may be carried out using a polyvinyl alcohol sponge, a nonwoven fabric, a nylon brush, or the like. The pH of the alkaline cleaning solution used in the alkaline cleaning step may be, for example, 7.5 or more, and from the viewpoint of improving cleaning properties, it is preferably 8.0 or more, more preferably 8.5 or more, for example 8.8 or more. In addition, from the viewpoint of preventing roughening of the substrate surface due to cleaning, the pH of the alkaline cleaning solution is usually 11 or less, preferably 10 or less, and more preferably 9.5 or less. As the alkaline cleaning solution, an aqueous solution containing one or more of the above-mentioned basic compounds can be used. Among them, an aqueous solution of an alkali metal hydroxide is preferred, and for example, an aqueous solution of potassium hydroxide can be preferably used. The alkaline cleaning step may be performed using a commercially available alkaline cleaning solution.

[0079] After the polishing using the polishing liquid is completed, the object to be polished may be washed with a non-alkaline rinse liquid before proceeding to the alkaline washing step. The rinse liquid may be water such as pure water or ion-exchanged water, or an acidic aqueous solution (e.g., an aqueous solution with a composition obtained by removing abrasive grains from the polishing liquid).

[0080] <Application> The polishing composition disclosed herein can be used for the finish polishing of a nickel-phosphorus-plated magnetic disk substrate (Ni-P substrate), and can effectively reduce scratch defects on the surface of the Ni-P substrate. The Ni-P substrate is typically a magnetic disk substrate having a nickel-phosphorus plating layer on the surface of the substrate. The material of the substrate can be, for example, an aluminum alloy, glass, glassy carbon, etc. The polishing composition disclosed herein can be preferably used for the finish polishing of a Ni-P substrate having a nickel-phosphorus plating layer on an aluminum alloy substrate.

[0081] According to this specification, a method for producing a Ni-P substrate comprising a final polishing step using the polishing composition disclosed herein and a preliminary polishing step performed prior to the final polishing step, and a Ni-P substrate produced by the method can be provided. Here, the final polishing step refers to the last polishing step in the manufacturing process of the target object (i.e., a step in which no further polishing is performed after that step). The Ni-P substrate manufacturing method may further include a cleaning step (e.g., an alkali cleaning step) performed after the final polishing step and a rough polishing step performed prior to the preliminary polishing step. The preliminary polishing step typically includes at least a first polishing step, and may further include a second, third, etc. polishing step. In these polishing steps, a polishing composition having a different composition from the polishing composition disclosed herein can be used.

[0082] The polishing composition disclosed herein can be preferably used, for example, for polishing a magnetic disk substrate (e.g., Ni-P substrate) whose surface roughness has been adjusted to 20 Å or less by an upstream process. Here, the surface roughness refers to the surface roughness (arithmetic mean roughness (Ra)) measured by a laser scanning surface roughness meter "TMS-3000WRC" manufactured by Schmitt Measurement System. It is particularly preferable to apply the composition to polishing a Ni-P substrate whose surface roughness has been adjusted to 10 Å or less. This allows Ni-P substrates with high quality surfaces to be produced with good productivity. EXAMPLES

[0083] Some examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples. In the following description, "parts" and "%" representing amounts used and contents are based on weight unless otherwise specified.

[0084] <Preparation of Polishing Composition> (Example 1) A polishing composition was prepared containing abrasive grains (4.9%), acid (1.5%), polyoxyethylene (POE) stearyl ether with 20 OE units (0.05 mM, 0.006%), hydrogen peroxide (0.4%) and deionized water, and adjusted to pH 2.0 with potassium hydroxide. Colloidal silica with an average primary particle size of 18 nm was used as the abrasive grains. Phosphoric acid (orthophosphoric acid) was used as the acid. The POE stearyl ether is a nonionic surfactant with an OE unit content of 77% (molecular weight 1150) and a structure in which an alkyl group with 18 carbon atoms and a polyoxyethylene chain are ether-bonded.

[0085] (Examples 2-7, 9, 10) Except that a nonionic surfactant of the type and content shown in Table 1 was used instead of the POE stearyl ether used in Example 1, a polishing composition according to each example was prepared in the same manner as in Example 1. The OE unit content, the number of OE units, the number of carbon atoms of the hydrocarbon group bonded to the polyoxyethylene chain, and the molecular weight of each additive are as shown in Table 1. Note that the number of carbon atoms shown in Table 1 is the total number in the case of an additive having two or more hydrophobic parts (Example 2).

[0086] (Example 8) A polishing composition according to this example was prepared in the same manner as in Example 1, except that POE stearyl ether was not used.

[0087] (Example 11) Except that polyethylene glycol with a molecular weight of 1000 (number of OE units: 23) was used instead of the POE stearyl ether used in Example 1, a polishing composition according to each example was prepared in the same manner as in Example 1.

[0088] (Example 12) A polishing composition according to this example was prepared in the same manner as in Example 1, except that 1H-benzotriazole was used instead of the POE stearyl ether used in Example 1 and its content was set to 0.01 mM.

[0089] <Polishing of Ni-P Substrate> Using the polishing composition according to each example as it is as a polishing liquid, polishing of the substrate to be polished was performed under the following conditions. As the substrate to be polished, an aluminum substrate for a hard disk (Ni-P substrate) having an electroless nickel-phosphorus plating layer on its surface, which was pre-polished so that the value of the surface roughness (arithmetic mean roughness (Ra)) measured by a laser scan type surface roughness meter "TMS-3000WRC" manufactured by Schmitt Measurement System was 6 Å, was used. The diameter of the above object to be polished was 3.5 inches (donut type with an outer diameter of about 95 mm and an inner diameter of about 25 mm), and the thickness was 1.27 mm. (Polishing Conditions) Polishing apparatus: Double-sided polishing machine, model "9B-5P", manufactured by Speedfam Polishing pad: Suede non-buff type Number of substrates to be polished: 10 ((2 substrates / carrier) x 5 carriers x 1 batch) Polishing fluid supply rate: 130mL / min Polishing load: 120g / cm 2 Lower surface plate rotation speed: 20rpm Polishing time: 5 minutes

[0090] <Cleaning> The polished Ni-P substrate was immersed in pure water and subjected to ultrasonic treatment at a frequency of 170 kHz, then immersed in an alkaline cleaning solution (a cleaning solution "CSC-102B" available from Speedfam Co., Ltd., diluted 200 times by volume) and scrubbed with a polyvinyl alcohol sponge while applying ultrasonic waves at a frequency of 170 kHz. The substrate was then immersed in pure water and subjected to ultrasonic treatment at a frequency of 950 kHz, and then pulled out into an isopropyl alcohol atmosphere and dried.

[0091] <Polishing rate> From the substrates obtained by polishing and cleaning with the polishing composition according to each example, randomly select 6 substrates (3 substrates / 1 batch), measure the weight loss of each substrate by polishing, calculate the polishing rate, and average the weight loss to obtain the polishing rate of each example.Specifically, the polishing rate is calculated based on the following formula: Polishing rate [μm / min] = weight loss of substrate due to polishing [g] / (substrate surface area [cm 2 ] × density of nickel phosphorus plating [g / cm 3 ] x polishing time [min] x 10 4 Here, the surface area of ​​one side of the board is 66 cm 2 , the density of nickel phosphorus plating is 7.9g / cm 3 The obtained values ​​were converted into relative values ​​with the value of Example 8 taken as 100%, and are shown in the column of "polishing rate relative value" in Table 1.

[0092] Based on the above relative values, the effect of the additive on the polishing rate was judged into the following three levels. The results are shown in the "Polishing rate judgment" column in Table 1. E: Relative value is 105% or more (excellent ability to suppress the decrease in polishing rate). G: Relative value is 95% or more and less than 105% (good ability to suppress the decrease in polishing rate). P: Relative value is less than 95% (poor ability to suppress the decrease in polishing rate).

[0093] <Scratch evaluation> A total of five substrates were randomly selected from the substrates obtained by polishing and cleaning with the polishing composition according to each example, and scratches on both sides of each substrate were detected under the following conditions. The total number of scratches on the five substrates (total of 10 sides) was divided by 10 to calculate the number of scratches per side of the substrate (number of scratches / side). The number of scratches thus obtained was converted into a relative value with the number of scratches in Example 8 taken as 100, and is shown in the "Scratch Relative Value" column in Table 1. (Scratch detection conditions) Measurement equipment: Candela OSA7100 manufactured by KLA-Tencor Corporation Spindle speed: 10,000 rpm Measurement range: 17000-47000μm Step size: 4μm Encoder multiplier:×16 Detection channel: P-Sc channel

[0094] Based on the above relative values, the degree of scratch reduction effect due to the use of the additive was judged into the following three levels. The results are shown in the "Scratch Evaluation" column in Table 1. E: Relative value is less than 65% (excellent scratch reduction ability). G: Relative value is 65% or more and less than 80% (good scratch reduction ability). P: Relative value is 80% or more (poor scratch reduction ability).

[0095] [Table 1]

[0096] As shown in Table 1, the polishing compositions of Examples 1 to 7 containing an additive corresponding to Additive A were able to reduce scratches without decreasing the polishing rate, compared with the polishing composition of Example 8 not containing the additive. On the other hand, the polishing compositions of Examples 9 to 12 using only an additive not corresponding to Additive A instead of the additive corresponding to Additive A did not have the effect of reducing scratches while suppressing the decrease in the polishing rate.

[0097] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes to the specific examples exemplified above. In addition, appropriate combinations of the above-mentioned aspects may also be included in the scope of the invention for which patent protection is sought by this application.

Claims

1. A polishing composition used for finish polishing of a nickel-phosphorus plated magnetic disk substrate, comprising: The method includes the steps of: The abrasive grains are silica grains, The average primary particle size of the abrasive grains is 1 nm or more and 50 nm or less, The additive A is a nonionic surfactant containing 85% by weight or less of oxyethylene units in the molecule, The content of the additive A is 0.01 mM or more and less than 0.08 mM, A polishing composition having a pH greater than 1.0 and not greater than 2.

5.

2. 2. The polishing composition according to claim 1, wherein the additive A is a compound having a structure in which an oxyethylene unit and a hydrocarbon group are bonded via an ether bond or an ester bond.

3. 3. The polishing composition according to claim 1, wherein the additive A is a compound having one or two chain hydrocarbon groups having 8 to 20 carbon atoms.

4. 4. The polishing composition according to claim 1, wherein the additive A is a compound having 25 or less oxyethylene units.

5. The polishing composition according to any one of claims 1 to 4, further comprising an oxidizing agent.

6. 6. A method for producing a magnetic disk substrate, comprising a step of finish-polishing a substrate to be polished with the polishing composition according to claim 1.

Citation Information

Patent Citations

  • Polishing liquid composition

    JP2007070548A

  • Polishing composition

    JP2007092064A

  • Polishing composition

    JP2009164186A

  • Polishing composition for nickel-phosphorus memory disks

    JP2012529133A

  • Polishing composition and method for producing polished article

    JP2016194004A